KEBIJAKAN PENGEMBANGAN PARIWISATA KABUPATEN JEMBER (Studi Kasus Strategi Pengembangan Wisata Pantai Puger Dalam Meningkatkan Kunjungan Wisatawan) - Masula, Imroatu Choiroh; Indartuti, Endang; Soenarjanto, Bagoes (JPAP: Jurnal Penelitian Administrasi Publik, 2017)
Attractions Puger Beach in Jember District, East Java Province. Puger Beach 35 km northwest of the city of Jember known as a fish auction, will Puger Beach has a very interesting beauty with a large waves also can be used for surfing. Another potential that can be developed is the island of Nusa Barong is located not far from Puger Beach, Development of attractions that must be done with more focused and sustainable.The formulation of this research is how is the strategy of puger beach tourism development in increasing the tourists in Jember District Government? So the purpose of the research is to analyze the strategy of puger beach tourism development in increasing the tourists. Sources of data in this study are primary data and secondary data. Primary data was obtained by conducting interviews to tourism managers, the public. Related offices and visitors who are in the location of research, while secondary data obtained from BPS, Department of Culture and Tourism Kab. Jember, libraries and internet, data analysis techniques used using Descriptive Analysis method while to obtain tourism development strategy using SWOT analysis.Based on the results of data analysis and discussion that has been done, it can be concluded tourism object. Puger Beach can be developed using aspects of attractiveness, accessibility aspects, aspects of activities and facilities, social, economic and cultural aspects. In addition, the output of this research is the making of policies and programs that can be used in the development of Puger Beach tourism destination.Â Keywords: Development Strategy, SWOT Analysis, Policy